Physical-chemical analysis of mixing water from an underground source after treatment with a ceramic filter - Automar Guédes de Lacerda Filho; Beatriz Wanderley Gomes; Maria Adriana de Freitas Mágero Ribeiro; Diego de Paiva Bezerra (Revista IBRACON de Estruturas e Materiais)
Abstract Civil engineering plays a pivotal role in advancing sustainability by offering increasingly viable and cutting-edge alternatives in materials management. In this context, the objective of this study is to assess the feasibility of reusing water for mixing concrete test specimens after employing a ceramic filter as a means of water purification. Additionally, we aim to compare the properties of the concrete and the chemical parameters of the water. To achieve this, a quantitative and qualitative investigation was conducted through laboratory tests to characterize the materials and perform a physical-chemical analysis of water from two samples sourced from the water table drawdown. One sample was in its raw form, while the other was treated with a ceramic filter. Mechanical strength tests were also carried out. Upon analyzing the obtained results, it was observed that the filtered water exhibited an 8.66% increase in compressive strength compared to the raw water. In the physical analysis of the water, both samples met the criteria for pH, color, and total dissolved substances. Furthermore, the chemical analysis of the water revealed a decrease in five out of the six parameters analyzed, specifically total alkalinity, chloride, phosphate, nitrate, sulfate, and zinc content. In conclusion, it can be inferred that there is potential to reduce certain elements in untreated water that adversely affect concrete strength and quality, in addition to improving the pH levels. Another noteworthy finding was the enhanced compressive strength of concrete when using treated water as opposed to raw water.